2020
DOI: 10.1097/sla.0000000000004179
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implant-associated Anaplastic Large Cell Lymphoma Incidence

Abstract: Objective: This study sought to estimate the incidence and incidence rate of breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) at a high-volume single institution, which enables vigorous long-term follow-up and implant tracking for more accurate estimates. Summary Background Data: The reported incidence of BIA-ALCL is highly variable, ranging from 1 in 355 to 1 in 30,000 patients, demonstrating a need for more accurate estimates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 29 publications
0
57
1
Order By: Relevance
“…Regarding the surgeons' preferences for a certain type of surface of breast implants, Nelson et al (18) noted that between 1991 and 2009, in the Memorial Sloan Kettering Cancer Center in the United States, textured implants by far exceeded smooth implants. Since 2009, a balance between the two types of implants was noticed, and after 2011, surgeons preferred smooth implants over textured implants (18). A multinational survey conducted in Europe and published in 2020 showed that most surgeons (70%) prefer textured implants and that only 29% of those who changed their preferences in terms of the implant surface and manufacturing company did so to prevent the occurrence of BIA-ALCL (28).…”
Section: New Approaches Of Cosmetic and Reconstructive Breast Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the surgeons' preferences for a certain type of surface of breast implants, Nelson et al (18) noted that between 1991 and 2009, in the Memorial Sloan Kettering Cancer Center in the United States, textured implants by far exceeded smooth implants. Since 2009, a balance between the two types of implants was noticed, and after 2011, surgeons preferred smooth implants over textured implants (18). A multinational survey conducted in Europe and published in 2020 showed that most surgeons (70%) prefer textured implants and that only 29% of those who changed their preferences in terms of the implant surface and manufacturing company did so to prevent the occurrence of BIA-ALCL (28).…”
Section: New Approaches Of Cosmetic and Reconstructive Breast Surgerymentioning
confidence: 99%
“…The average exposure time was 10.26 (range: 6.4-15.5) years. The overall incidence of BIA-ALCL was 1.79 per 1000 patients with textured implants (1:559) and 1.15 per 1,000 textured implants (1: 871) -the difference is caused by the fact that several patients were exposed to more than one implant in their lifetime(18). After analyzing a cohort of 3,546 patients who also benefited fromTable 1.…”
mentioning
confidence: 99%
“…The incidence of this lymphoma is difficult to calculate. In the U.S. its incidence has been estimated at 1 in 6120 women with breast implants per year, and 1 in 4120 women with textured breast implants per year, with a cumulative incidence of 3.31 per 1000 breast implants between 14 and 16 years after surgery [ 150 ].…”
Section: Breast Implant-associated Alclmentioning
confidence: 99%
“…14 Current estimates of lifetime risk for BIA-ALCL in patients with textured implants range from 1-in-559 to 1-in-355. 15,16 When screening for BIA-ALCL, the primary care provider should ask the patient about texturing of the implant, the manufacturer of the implant, and the duration of implant placement. 17 On physical exam, BIA-ALCL commonly presents as new breast swelling or fluid collection 7-10 years after implant insertion, but it can also present as a new mass or capsular contracture.…”
Section: General Breast Implant Carementioning
confidence: 99%